PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK YOGHURT REPUBLIC DI LEGIAN (Studi Pada Yoghurt Republic Legian) - Ni Kadek Ary Ervikayanti; Ida Ketut Kusumawijaya (Universitas Triatma Mulya, 2020)
Purchasing decisions are actions of consumers to want to buy or not on the products offered. From various factors that influence consumers in determining the purchasing decision of a product, usually consumers always consider product quality and price. The problem raised in this study is whether product quality (X1) influences purchasing decisions (Y) on Yoghurt Republic products in Legian. Does the price (X2) affect the purchasing decision (Y) on Yoghurt Republic products in Legian. How big is the influence of product quality (X1) and price (X2) on purchasing decisions (Y) on Yoghurt Republic products in Legian, and which independent variable has the dominant influence on purchasing decisions (Y) on Yoghurt Republic products in Legian. The population in this study amounted to 120 respondents with a minimum age of 15 years. The data analysis technique used is quantitative descriptive analysis, validity and reliability test data, classic assumption test, multiple linear regression test, t test analysis, coefficient of determination analysis, and test analysis of the dominant variable influential (β). The results of the analysis show the regression results of Y = 4.963 + 0.466 X1 + 0.206 X2. The conclusions obtained are product quality (X1) has a positive and significant effect partially on purchasing decisions (Y) indicated by the regression coefficient b1X1 which is positive at 0.466 with a tcount = 7.893> t table = 1.661 with a sig = 0,000. Price (X2) has a positive and significant effect partially on purchasing decisions (Y) indicated by the regression coefficient b2X2 which is positive at 0.206 with a value of t = 2.520> t table = 1.661 with a sig value = 0.013. The magnitude of the influence of product quality and price on purchasingdecisions is 67.5% and the remaining 32.5% is influenced by other variables not discussed in this study. The independent variable that has the dominant influence on purchasing decisions can be seen from β (beta) is the product quality variable which is equal to 0.575 while the price variable is 0.184.